2020
DOI: 10.1186/s13054-020-03220-x
|View full text |Cite
|
Sign up to set email alerts
|

Auxora versus standard of care for the treatment of severe or critical COVID-19 pneumonia: results from a randomized controlled trial

Abstract: Background: Calcium release-activated calcium (CRAC) channel inhibitors stabilize the pulmonary endothelium and block proinflammatory cytokine release, potentially mitigating respiratory complications observed in patients with COVID-19. This study aimed to investigate the safety and efficacy of Auxora, a novel, intravenously administered CRAC channel inhibitor, in adults with severe or critical COVID-19 pneumonia. Methods: A randomized, controlled, open-label study of Auxora was conducted in adults with severe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 20 publications
0
48
1
2
Order By: Relevance
“…A previous study reported that there were proportionally fewer well-designed RCTs published during an urgent situation. Chang et al [36] found that among 338 COVID-19 registered trials, only 16 had adopted randomized, single-blind or double-blind designs, and only 8 studies had used randomized, double-blind, placebo-controlled design. Xie et al [37] also found that RCT was the most common design in 51 pilot studies, but only 10 of those studies had used blinding.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that there were proportionally fewer well-designed RCTs published during an urgent situation. Chang et al [36] found that among 338 COVID-19 registered trials, only 16 had adopted randomized, single-blind or double-blind designs, and only 8 studies had used randomized, double-blind, placebo-controlled design. Xie et al [37] also found that RCT was the most common design in 51 pilot studies, but only 10 of those studies had used blinding.…”
Section: Discussionmentioning
confidence: 99%
“…In an RCT on severe or critical COVID-19, the proportion of patients who received invasive MV or died was lower in the Auxora-treated group than the control group (3 out of 17 [18%] vs. 5 out of 9 [6%]; HR 0.23, 95% CI 0.05 to 0.96; P < 0.05) and the mean difference in the 8-point ordinal scale was statistically significant on day 6 and day 9 to 12 ( P < 0.05) 79 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that Auxora may protect against pulmonary endothelial damage and cytokine storm 119 , 120 . This agent has been shown to be effective in terms of survival and clinical improvement in one small-scale RCT for severe or critical COVID-19 79 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 74 studies 2, 5, 15-18, 36-39, 41-44, 47-54, 56, 57, 59-63, 65-67, 69, 70, 72, 74-76, 78, 79, 82, 83, 85, 87, 88, 90-92, 94-97, 99, 100, 103-121, 125 including 48622 patients reported all-cause mortality. After filtering out treatments with small sample size following the specified criteria, the network included azithromycin, hydroxychloroquine, hydroxychloroquine plus azithromycin, colchicine, arbidol (umifenovir), favipiravir, remdesivir, lopinavir/ritonavir, convalescent plasma, methylprednisolone, dexamethasone, hydrocortisone, immunoglobulin, interferon beta, recombinant human granulocyte colony-stimulating factor (GCSF), tocilizumab, vitamin D 3 , baricitinib plus remdesivir, sulodexide and SOC.…”
Section: Resultsmentioning
confidence: 99%